Profile of leprosy patients: a literature review (Research, Society and Development, 2021)
Objective: To analyze the profile of patients with leprosy who are treated by the Brazilian Unified Health System. Methodology: This is an integrative literature review, carried out in the Web of Science, US National Library of Medicine (PubMed) and Latin American and Caribbean Literature in Health Sciences (LILACS) databases, from the selection of indexed descriptors and their synonyms, which combined through the Boolean operators AND and OR constituted the search expression, representing the guiding question. Full articles published between 2010 and 2021 in English, Portuguese or Spanish were included. Results: 73 scientific publications were found, from the information on the criteria, 13 were selected for full reading. Nine of these articles were considered for this study which profile of leprosy patients is aged between 37 and 49.28 years, male, urban residents, incomplete primary education, retirees and housewives who lived with a value between one and three algorithms, new cases that were mostly referred from other services, borderline clinical forms, dimorphic, unclassified and indeterminate, paucibacillary and zero degree of physical disability. Conclusion: In view of these findings, this study identified the epidemiological profile of the majority of patients affected by leprosy in Brazil, stressing the importance of articulation of services, adequate case management and effectiveness of health surveillance actions, whose role should be played by the Primary Health Care.